Protein kinases and the regulation ofmRNA splicing and translation. - Stojdl, David F. (University of Ottawa (Canada), 2000)
Regulation of genetic information occurs through many intricate and varied mechanisms. We have explored two such mechanism, splicing and translation initiation, by studying two kinase families involved in these processes. The work in this thesis represents our ongoing efforts to understand the role of these proteins and the mechanisms by which they work. In the first section of this thesis, we present evidence that the Clk family of kinases are able to influence the regulatory process known as alternative splicing. In the second portion, we discuss PKR, a regulator of protein translation, and demonstrate it to be an essential mediator of antiviral defence. In the final chapter, we consider a possible application of the data from our PKR studies, and propose an oncolytic therapy based on putative defects in regulatory pathways controlling PKR and other members of the IFN pathway.
Keywords: Biology, Molecular.